Types of Fungi Species Attacking Mulberry, Symptoms, and Their Interaction - Karthick Mani Bharathi B; Susikaran S; Kiruthika C; Vasanth V; Ramya Harika K (International Journal of Fungi, 2025)
Mulberry trees (Morus spp.) are essential in sericulture since their leaves are the primary source of nutrition for silkworms (Bombyx mori L.). The cultivation of mulberry trees has long been integral to the silk industry, particularly in countries like China, India, and Japan. However, like all agricultural crops, mulberry trees are vulnerable to a variety of pests and pathogens including fungi. Fungal diseases can have a profound impact on mulberry trees thus leading to reduced leaf quality, stunted growth, and even death of the tree in severe cases. Fungal infections not only affect the health of the mulberry trees but also have direct consequences on the silkworm industry. Healthy mulberry trees are necessary to sustain the silkworm population and produce high-quality silk. As such, understanding the types of fungi species that attack mulberry, the symptoms of fungal infections and how these pathogens interact with mulberry trees is essential for effective management and prevention strategies. This article will discuss various fungal species that attack mulberry trees, outline the symptoms they cause, and explore their interactions with mulberries. We will also cover the importance of fungal control in sericulture and provide insights into integrated management strategies.
Keywords: Disease management; disease symptoms; fungal pathogens; fungal-plant interaction; mulberry diseases; root rot fungi